Translation of Historical Realias and Archaisms in V. Pikul’s Novel “The Favorite” - Tsaturyan, Lilit (Bulletin of Yerevan University B: Philology, 2025)
During the translation of historical novels and historical works lexical transformations are inevitable especially because the main means of linguistic stylization of the period depicted in the text are lexical and grammatical archaisms, the translation of which is very difficult. During the translation of historical works the translation of historisms and archaisms is especially important because there is a big and important problem of conveying the national and historical flavor of the original language. In the theory of translation two ways of conveying the realia are usually distinguished: transcription and translation. In the Armenian translation of V. Pikul's novel “The Favorite” the translator V. Vardanyan used the mentioned versions of conveying historical realia and archaism due to a number of circumstances. In those cases, when it was necessary to depict and strongly emphasize the historical flavor of the novel, the environment of the era the translator retained the realia by simply transcribing it without additional explanations, and in some cases giving its description. The translation of the realia perceived in the Armenian reality is more successful. In some cases, realia is replaced by a neutral equivalent or by the realia familiar to the reader, but the replaced forms are either not archaisms or lack stylistic coloring.
Keywords: lexical transformation; historical novel; historism; archaism; realia; transcription; calque; equivalence